2021
DOI: 10.1038/s41598-021-85735-z
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeographic history of Krascheninnikovia reflects the development of dry steppes and semi-deserts in Eurasia

Abstract: Constituting one of Earth’s major biomes, steppes are characterised by naturally treeless extra-tropical vegetation. The formation of the Eurasian steppe belt, the largest steppe region in the world, began in Central Asia during the Neogene. In the glacial stages of the Pleistocene, steppe displaced forest vegetation, which in turn recolonised the area during the warmer interglacial periods, thus affecting the distribution of plants adapted to these habitats. Krascheninnikovia ceratoides (Chenopodiaceae) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…The Eurasian steppe belt was under strong influence of the Pleistocene glaciations that caused extensive expansions and contractions as well as latitudinal shifts and longitudinal splits of the ranges of steppe plant species during the past 3 million years (Hurka et al., 2019 and references therein). It has been shown that such a biome dynamic is mirrored by molecular signals of typical Eurasian steppe plants (e.g., Capsella orientalis ) and thus reflects their biogeographical history (Buono et al., 2021 ; Franzke et al., 2004 ; Friesen et al., 2016 , 2020 ; Hantemirova et al., 2020 ; Hurka et al., 2012 ; Seidl et al., 2019 , 2021 ; Seregin et al., 2015 ; Volkova et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Eurasian steppe belt was under strong influence of the Pleistocene glaciations that caused extensive expansions and contractions as well as latitudinal shifts and longitudinal splits of the ranges of steppe plant species during the past 3 million years (Hurka et al., 2019 and references therein). It has been shown that such a biome dynamic is mirrored by molecular signals of typical Eurasian steppe plants (e.g., Capsella orientalis ) and thus reflects their biogeographical history (Buono et al., 2021 ; Franzke et al., 2004 ; Friesen et al., 2016 , 2020 ; Hantemirova et al., 2020 ; Hurka et al., 2012 ; Seidl et al., 2019 , 2021 ; Seregin et al., 2015 ; Volkova et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…et Kir. [ 28 ]; A. obliquum L. [ 59 ], and also in other plant groups: genera Krascheninnikovia (family Amaranthaceae) [ 60 ] and Goniolimon (family Plantaginaceae) [ 61 ]. All this confirms the complex phylogenetic history of the steppe flora [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same region of origin, for example, is reported for Krascheninnikovia ceratoides (L.) Gueldenst. [ 22 , 23 ], a species also belonging to Axyrideae [ 13 ]. It is still not clear whether the origin of Axyris and Krascheninnikovia is linked to high-altitude or lowland steppes, but it is thought that the late Miocene and early Pliocene are the time scales where a continent-wide restructuring of the distribution of landscape-forming elements was taking place, including a new zonal structure component: steppe formation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%